IMPLEMENTASI RESEACH AND DEVELOPMENT DALAM PERANCANGAN ADMINISTRASI KEUANGAN SEKOLAH BERBASIS MULTI USER - Irene Ongkowijoyo (Pusat Riset dan Inovasi Nasional, 2021)
The application of computer-based information systems results in processing data into information that can be done quickly and accurately. At SMP insan Mulia Bandung the problems that arise are the manual processing of school financial administration data, causing the recording of receipts and expenditures to take a long time, frequent delays in making reports, errors in calculating transactions, and storing data separately. difficult to find data. The purpose of this study is to design a school financial administration information system at SMP insan Mulia Bandung which facilitates data processing of school financial administration data. The research method used is RnD (Reseach and Development), through the following steps: problem identification, collecting information, product design, design validation, design improvement, initial product trial, product revision, usage trial, final product revision, and product manufacture. The resulting program is built using the Microsoft Visual Basic 6.0 programming language with MySQL database. The implementation of the resulting information system is expected to facilitate the processing of school financial administration data, quickly and accurately in making reports and facilitating data retrieval.